2020
DOI: 10.1186/s12865-020-00378-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell levels in adults living with type 2 diabetes: a systematic review and meta-analysis of clinical studies

Abstract: Background Chronic immune activation and hyperglycaemia are a hallmark of type 2 diabetes mellitus (T2D) while natural killer (NK) cells are involved in the pathogenesis of T2D. Dysregulated NK cell responses are associated with an increased risk of cardiovascular disease in patients living with T2D. Objective To provide a comprehensive and systematic evidence-based estimate on the levels of NK cells in patients living with T2D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Various studies have evaluated the levels of NK cells in patients with T2DM. 25,26 Our findings are consistent with those of a study that reported a reduction in NK-cell expression. 25 In that study, the level of NK cells was found to be associated with the level of HbA1c.…”
supporting
confidence: 91%
“…Various studies have evaluated the levels of NK cells in patients with T2DM. 25,26 Our findings are consistent with those of a study that reported a reduction in NK-cell expression. 25 In that study, the level of NK cells was found to be associated with the level of HbA1c.…”
supporting
confidence: 91%
“…A recently published meta-analysis, collecting results from 13 independent studies, showed that circulating NK cells number increase in T2D patients (n=491), compared to healthy subjects (n=1607) ( 115 ) ( Figure 2A ) . However, other studies showed no differences in the phenotype between NK cells in T2D and NK cells in healthy controls ( 116 ).…”
Section: Introductionmentioning
confidence: 99%
“…The data on human NK cells is somewhat unclear. Meta-analysis of 13 NK cell studies identified 3 with decreased levels/activity, 2 reported elevated levels and 8 of them reported no differences between circulating NK cells in T2D patients and healthy controls ( 52 ).…”
Section: Discussionmentioning
confidence: 99%